Human trafficking: A review of the crime in Odisha, India. (December 2020) - Kumar, Rohan; Mishra, Niharranjan; Mishra, Pooja Shree
Abstract: Human trafficking is a multi-layered criminal offence that has plagued India and people in the Odisha (State in the Republic of India) are at an alarming risk of trapped in trafficking. Trafficking takes several forms of exploitation, ranging from forced servitude to commercial sexual exploitation in the state. Owing to its high rural population, Odisha has emerged as a source for trafficking in the last decade. This study analyses the secondary data from various online sources and addresses the major causes which encourages the traffickers to trap more people in the racket of trafficking. It also provides a statistical analysis of the crime in the state with major stakeholder analysis followed by a comparative study of the anti-trafficking model used in the north-eastern states of India. It also addresses the vulnerabilities of the victims who are forced into trafficking and the socio-economic factors that contribute to their vulnerabilities. The article outlines several central and state anti-trafficking legal policies which range from countering trafficking to the successful rehabilitation of the victims. Analysing the several sociological aspects which catalyse the process of trafficking in the community, the study aims to paint a clearer picture of the scenario of trafficking in Odisha whilst recognising the vulnerable people based on the rescue operations made by the state government.